A Perspective on Reprioritizing Children’s’ Wellbeing Amidst COVID-19: Implications for Policymakers and Caregivers - Chaturvedi, Shakti; Pasipanodya, Thomas Enias (Frontiers in Human Dynamics, 2021)
The present work presents an analytical and investigatory view of the existing issues regarding COVID-19 with attention to children and their overall well-being during the second quarter of 2020. The authors conducted an extensive content analysis of media reports, government briefings, social platforms, and provide some recommendations to the policymakers and care providers for building more robust responses for the pandemic affected children. The article contributes to the existing field of study in the following ways. Firstly, the present manuscript describes the impact of COVID-19 on the psychosocial health of children. Secondly, the authors offered some outcome-based responses to policymakers and caregivers to mitigate the negative impact of the pandemic on COVID affected families and children. Thirdly, the article highlights the importance of social media, the role of storytelling, and using the concept of mandalas in handling the pandemic affected sensitive sections of the society. Lastly, the authors furnish some response initiatives to combat the novel COVID-19 pandemic based on real-world observations. These initiatives can influence policymakers as well as help caregivers to design efficient and adequate response programs for the pandemic affected children.